2016
DOI: 10.1016/j.theriogenology.2016.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of pioglitazone on metabolism, milk yield, and reproductive performance in transition dairy cows

Abstract: 27The objective of this study was to investigate the effect of dietary supplementation of 28 pioglitazone (PGT), a specific ligand for PPARγ, on metabolic dynamics, milk production, 29 and reproductive performance of transition dairy cows. Eighty multiparous Holstein cows in 30 their second or more lactations were blocked by the calving date and parity and assigned 31 randomly to four dietary groups (n=20 cow/treatment) including control (no PGT-/-), 32supplemented with PGT (6 mg PGT/kg body weight) from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 54 publications
9
16
0
Order By: Relevance
“…We did not observe any significant effect of TZD on insulin sensitivity indexes, with only numerically greater QUICKI compared to control animals prior to IMI. Lack of effect on insulin sensitivity indexes in our study is in accordance with data in dairy cows from Schoenberg and Overton [73], where the TZD was used before birth, and Yousefi and collaborators [74], where pioglitazone, another thiazolidinedione and a well-established synthetic PPAR γ ligand, was used during the entire transition period.…”
Section: Discussionsupporting
confidence: 90%
“…We did not observe any significant effect of TZD on insulin sensitivity indexes, with only numerically greater QUICKI compared to control animals prior to IMI. Lack of effect on insulin sensitivity indexes in our study is in accordance with data in dairy cows from Schoenberg and Overton [73], where the TZD was used before birth, and Yousefi and collaborators [74], where pioglitazone, another thiazolidinedione and a well-established synthetic PPAR γ ligand, was used during the entire transition period.…”
Section: Discussionsupporting
confidence: 90%
“…In line with Smith et al (2007) and Yousefi et al (2016), results of the present study showed that dietary PGT and WM during the first 21 d of postpartum had no effect on milk yield and milk composition. It is well documented that there is a relationship between the BCS at calving and BCS loss postpartum.…”
Section: Discussionsupporting
confidence: 91%
“…This result may be ascribed to the short duration of the dietary supplementation. Yousefi et al (2016) who fed 6 mg PGT for a 35 d period reported higher plasma IGF-1 in transition dairy cows.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The most striking finding of the present study was the effect of PBLC+B on BW. Because of a negative energy balance, high-yielding dairy cows typically lose between 40 and 70 kg BW at one to two months after calving [ 60 62 ]. A weight loss of ~70 kg was also observed in the CON and MON groups in Phase 3 of the present study.…”
Section: Discussionmentioning
confidence: 99%